If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + -1) + -2x + 5 = 4(x + -2) + 4 Reorder the terms: 3(-1 + x) + -2x + 5 = 4(x + -2) + 4 (-1 * 3 + x * 3) + -2x + 5 = 4(x + -2) + 4 (-3 + 3x) + -2x + 5 = 4(x + -2) + 4 Reorder the terms: -3 + 5 + 3x + -2x = 4(x + -2) + 4 Combine like terms: -3 + 5 = 2 2 + 3x + -2x = 4(x + -2) + 4 Combine like terms: 3x + -2x = 1x 2 + 1x = 4(x + -2) + 4 Reorder the terms: 2 + 1x = 4(-2 + x) + 4 2 + 1x = (-2 * 4 + x * 4) + 4 2 + 1x = (-8 + 4x) + 4 Reorder the terms: 2 + 1x = -8 + 4 + 4x Combine like terms: -8 + 4 = -4 2 + 1x = -4 + 4x Solving 2 + 1x = -4 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 2 + 1x + -4x = -4 + 4x + -4x Combine like terms: 1x + -4x = -3x 2 + -3x = -4 + 4x + -4x Combine like terms: 4x + -4x = 0 2 + -3x = -4 + 0 2 + -3x = -4 Add '-2' to each side of the equation. 2 + -2 + -3x = -4 + -2 Combine like terms: 2 + -2 = 0 0 + -3x = -4 + -2 -3x = -4 + -2 Combine like terms: -4 + -2 = -6 -3x = -6 Divide each side by '-3'. x = 2 Simplifying x = 2
| 4s-11=41 | | -0.2p+100=-0.25+0.05p | | -y=-9-3x | | 25=b-9 | | 9-b=29 | | 3x-11=52 | | 36y^2+16=0 | | 8y-15=41 | | -7+6-20-(-8)= | | -5x+9=4x-54 | | (12+3+5k)6+4k+2(k+5)= | | Y+.15=11 | | (-2y)-3y+8=8-5y-12 | | 12+3y=7x | | -0.2p+100=y | | 4(2y-3)=2(3y-2) | | -x+4=2x-r | | 7x-16=16+5x | | 20y+5=p | | 5n-12=(-3)+4 | | 4x+2*5x+5= | | 14x+40=22x | | 2*(x+10)=4*x | | 25=10x+5 | | 12=-1+1 | | 2(x+10)=4*x | | 37t-25=9t-13 | | 112=6x+4y | | 46=47-1x | | 10(y+3)=40 | | 4-3*-5=Y | | 240+0.15x=357 |